National Practice on State Entities in The Republic of Uzbekistan in Light of International Commercial Arbitration (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This paper analyzes national legislation on State entities in Uzbekistan. Following to this, the research examines the development stages of international commercial arbitration practice in Uzbekistan and potential case between Romak SA v the Republic of Uzbekistan in the scope of international commercial arbitration. As an important goal of this paper, the significant recommendations in further development of international commercial arbitration practice in Uzbekistan will be provided accordingly.